Photoelastic Stress Analysis Surrounding Implant-Supported Prosthesis and Alveolar Ridge on Mandibular Overdentures - Dorival Pedroso da Silva; Claudia Cazal; Fernanda Campos Sousa de Almeida; Reinaldo Brito e Dias; Rafael Yagüe Ballester (Hindawi Limited, 2010)
The purpose of this research was to evaluate the maximum stress around osseointegrated implants and alveolar ridge, in a mandible with left partial resection through a photoelastic mandibular model. The first group consisted of two implants: traditional model (T), implants placed in the position of both canines; fulcrum model (F), implants placed in the position of left canine CL and right lateral incisor LiR. Both models linked through a bar and clips. The second group was consisted of three implants, with implants placed in the position of both canines (CR and CL) and the right lateral incisor (LiR), which composed four groups: (1) model with 3 "O" rings, (2) model 2 ERAs, bar with clips, (3) model 2 ERAs bar without clips; (4) model "O" ring bar and ERA. An axial and an oblique load of 6.8 kgf was applied on a overdenture at the 1st Pm, 2nd Pm, and 1st M. Results showed that the area around the left canine (CL) was practically free of stress; the left lateral incisor (LiL) developed only small tensions, and low stress in all the other cases; the right canine tooth suffered the largest concentrations of stress, mainly with the ERA retention mechanism.